2020
DOI: 10.1007/s10597-020-00602-x
|View full text |Cite
|
Sign up to set email alerts
|

Disseminating Trauma-Focused Cognitive Behavioral Therapy with a Systematic Self-care Approach to Addressing Secondary Traumatic Stress: PRACTICE What You Preach

Abstract: This pilot study evaluated the effectiveness of Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) training programs augmented with a systematic “PRACTICE What You Preach” (PWYP) self-care focus, which has trainees personally utilize the coping skills they teach their clients. Participants were 115 clinicians/supervisors who completed a PWYP TF-CBT training program. Pre- to post-training analyses documented significant increases in participants’ competency and fidelity in implementing TF-CBT (ps < .001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 52 publications
5
13
1
1
Order By: Relevance
“…Lastly, we assessed the clinicians’ experience of stress as well as their challenges in implementing self-care during the pandemic. Research has established that the stress level and coping resources of clinicians can significantly impact the quality of services provided by them to their traumatized clients ( Deblinger et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we assessed the clinicians’ experience of stress as well as their challenges in implementing self-care during the pandemic. Research has established that the stress level and coping resources of clinicians can significantly impact the quality of services provided by them to their traumatized clients ( Deblinger et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such interventions should be based on empirical findings relevant to professional wellbeing in CAMHS. For example, a recent study [ 85 ] found potential benefits from combining a self-care approach, referred to as “PRACTICE What You Preach” into TF-CBT training for reducing level of secondary traumatic stress. Although therapist directed interventions like this or mindfulness training can help, previous studies have shown that organizational interventions are more alterable and are more efficient in reducing burnout and increase personal efficacy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Erste Untersuchungen zeigen, dass sich durch ein Tf-KVT Training das Selbstwirksamkeitserleben von Thera-peut_innen in ihrem Einbezug von Bezugspersonen verbessern lässt (Woody, Anderson & D'Souza, 2015). Die Kombination einer Tf-KVT Fortbildung mit einem Selbstfürsorge-Ansatz führte zu einem größeren traumatherapeutischen Kompetenzerleben und einer geringeren Belastung (Deblinger, Pollio, Cooper & Steer, 2020…”
Section: Diskussionunclassified